Sustainable power sources based on high efficiency thermopower wave devices. Issue 4 (21st January 2016) - Mahajan, Sayalee G.; Liu, Albert Tianxiang; Cottrill, Anton L.; Kunai, Yuichiro; Bender, David; Castillo, Javier; Gibbs, Stephen L.; Strano, Michael S.
Abstract : Thermopower wave devices are shown to achieve over 1% chemical-to-electrical conversion efficiency, producing energy densities on par with Li-ion batteries. Abstract : There is a pressing need to find alternatives to conventional batteries such as Li-ion, which contain toxic metals, present recycling difficulties due to harmful inorganic components, and rely on elements in finite global supply. Thermopower wave (TPW) devices, which convert chemical to electrical energy by means of self-propagating reaction waves guided along nanostructured thermal conduits, have the potential to address this demand. Herein, we demonstrate orders of magnitude higher chemical-to-electrical conversion efficiency of thermopower wave devices, in excess of 1%, with sustainable fuels such as sucrose and NaN3 for the first time, that produce energy densities on par with Li-ion batteries operating at 80% efficiency (0.2 MJ L −1 versus 0.8 MJ L −1 ). We show that efficiency can be increased significantly by selecting fuels such as sodium azide or sucrose with potassium nitrate to offset the inherent penalty in chemical potential imposed by strongly p-doping fuels, a validation of the predictions of Excess Thermopower theory. Such TPW devices can be scaled to lengths greater than 10 cm and durations longer than 10 s, an over 5-fold improvement over the highest reported values, and they are capable of powering a commercial LED device. Lastly, a mathematical model of wave propagation, coupling thermal and electron transport with energy losses, is presented to describe the dynamics of power generation, explaining why both unipolar and bipolar waveforms can be observed. These results represent a significant advancement toward realizing TPW devices as new portable, high power density energy sources that are metal-free.